Measuring Quality Work-Life of Teachers in Higher institutions – An Indian Perspective - K.V, Ramegowda; Kumari , Anitha (Journal of Ecohumanism, 2024)
The research paper attempts to reveal the work-life balance among faculty working in educational institutions around rural Bengaluru. It also examines the factors affecting their work and personal life during their life span. The present study will bring new insights and their relationship between these factors and quality of work life (QWL). The variables taken for the study are organization support, job enrichment, job satisfaction, work domain, stress and work life. An exploratory and descriptive research design technique is adopted—the primary data collected through a structured questionnaire using Google forms. A five-point Likert-scale is used to measure the QWL variables. Among the five dimension of QWL, it is evident from the results that organizational support (R square value 0.67) is highly associated with QWL followed by Work condition (R2 = 0.58). Through this study, the management can identify the variables that influence the QWL and try to overcome the issues, leading to employee performance, job satisfaction, retaining, and reduction in overhead. The main purpose of the study is to measure the Quality of Work Life of teachers of private institutions located at Bengaluru Rural region. Also, we analysed the Quality of Work Life across various variables among teaching employees of the private colleges/universities.